EFEKTIFITAS PENGGUNAAN MEDIA ZOOM DALAM MENINGKATKAN HASIL BELAJAR PAI MATERI MEYAKINI ALLAH MAHA ESA DAN MAHA PEMBERI - Yuyun Nisfu Laila (STAI Ma'had Aly Al-Hikam Malang, 2021)
This research is a Classroom Action Research which aims to determine the improvement of learning outcomes in the matter of believing in Allah Almighty and the Most Giver in SD Negeri 1 Sidodadi, Gedangan District, Malang Regency by learning to use the media zoom. This research is a descriptive quantitative research with data collection using observation and documentation methods. Based on the data obtained from the observation results, the average pretest score is 60 with a student learning completeness percentage of 33,33%, the average test score in the first cycle is 67,5 with a student learning completeness percentage of 58,33% and the average test score in the second cycle of 70,8 with a percentage of student learning completeness of 66,66%, it can be concluded that the use of zoom media in learning that has been carried out at SD Negeri 1 Sidodadi, Gedangan District is very effective in improving PAI learning outcomes in terms of believing in Allah Almighty and the Most Giver.